EAU-ESPU pediatric urology guidelines on testicular tumors in prepubertal boys. Issue 4 (August 2021) - Stein, Raimund; Quaedackers, Josine; Bhat, Nikita R.; Dogan, Hasan S.; Nijman, Rien J.M.; Rawashdeh, Yazan F.; Silay, Mesrur S.; 't Hoen, Lisette A.; Tekgul, Serdar; Radmayr, Christian; Bogaert, Guy
Summary: Background: Testicular tumors in prepubertal boys account for 1–2% of all solid pediatric tumors. They have a lower incidence, a different histologic distribution and are more often benign compared to testicular tumors in the adolescent and adult group. This fundamental difference should also lead to a different approach and treatment. Objective: To provide a guideline for diagnosis and treatment options in prepubertal boys with a testicular mass. Method: A structured literature search and review for testicular tumors in prepubertal boys was performed. All English abstracts up to the end of 2019 were screened, and relevant papers were obtained to create the guideline. Results: A painless scrotal mass is the most common clinical presentation. For evaluation, high resolution ultrasound has a detection rate of almost 100%, alpha-fetoprotein is a tumor marker, however, is age dependent. Human chorionic gonadotropin (HCG) was not a tumor marker for testis tumors in prepubertal boys. Conclusion: Based on a summary of the literature on prepubertal testis tumors, the 2021 EAU guidelines on Pediatric Urology recommend a partial orchiectomy as the primary approach in tumors with a favorable preoperative ultrasound diagnosis.